Large State Variation in Sugar-Sweetened Beverage Purchases: What We Learn from the Beverage Industry Data. Issue 12 (16th December 2021) - Andreyeva, Tatiana
ABSTRACT: Negative health consequences of excessive sugar-sweetened beverage (SSB) consumption have prompted recommendations for SSB taxation to improve diet and health. Over 40 countries and 8 local US jurisdictions have implemented SSB taxes to date. There is considerable interest in state SSB taxes in the USA, but state-level data on SSB consumption levels is lacking. This article uses proprietary data from the Beverage Marketing Corporation on beverage sales across all US retail channels to estimate state-level per capita SSB purchases in 2021. There is considerable variation in per capita SSB purchases across states, from an estimated annual 23.5 gallons (89.1 L) in Hawaii to 51.8 gallons (196.1 L) in Missouri. Current average levels of SSB purchases at 13 ounces (0.38 L) daily leave little to no room for added sugars from all other sources. Policymakers in states with extra-high SSB purchases, especially in the Midwest, should consider effective evidence-based policies, including fiscal approaches, to increase awareness about SSB risks, encourage healthier beverage choices, and improve population diet. Abstract : This brief communication uses proprietary industry data to inform state public policy about current high levels of purchases of sugar-sweetened beverages and their substantial variation across states.